A quality improvement project to assess the feasibility and practicability of training women and their relatives about home blood pressure monitoring - Anand, Upali; Samant, Padmaja; Mehta, Alisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Women with hypertensive pregnancies have a higher chance of developing subsequent hypertension, chronic renal disease and stroke. Lack of blood pressure (BP) monitoring in the postpartum period, only augments this risk. Keeping this is mind, this study was formulated, to enable women to timely detect any such complication later on in their life. Methods: In a tertiary healthcare hospital, postpartum women with hypertension in pregnancy and their relatives were sought consent from, enrolled into the study and trained on self-BP monitoring using an electronic BP measuring device. The feasibility outcome measures were “ease of use” of device by the participant, and the ability to correctly measure blood pressure with appropriate reporting of the value. Results: A total 47 pairs of women and their relatives participated in this study, at the end of which, 89.4% of the patients and 78.7% of the relatives were able to handle the device properly and take their own BP, with appropriate interpretation of the value. Participants who had a higher level of education were more likely to have understood the significance of the practice and comply with it. Moreover, about 70% of patients’ and 72% of relatives were willing for home blood pressure monitoring (HBPM). Conclusions: Feasibility and practicability of training women/relatives about home blood pressure monitoring were demonstrated in this study. Thus, a postpartum remote hypertension monitoring programme, which involves educating the patient and their family members to enable them to monitor their BP at home or a nearby primary centre, is the need of the hour.